2016
DOI: 10.11114/jets.v4i7.1477
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of High School Curricula Employing Using the Element-based Curriculum Development Model

Abstract: This study was conducted with the aim of evaluating the curricula that constitute the basis of education provision at high schools in Turkey from the perspective of the teachers involved. A descriptive survey model, a quantitative research method was employed in this study. An item-based curriculum evaluation model was employed as part of the evaluation process. The data for the study were obtained from the 199 participant teachers via an "evaluation questionnaire of the high school curriculum. This questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…Results indicated that teachers highly observed the integration of national goals and the DepEd's Mission and Vision in the HUMSS curriculum. This result is consistent with Leduc (2010), however it was again in contrast to Aslan and Günay (2016), where teachers only viewed these elements as moderately observed. Similarly, Gallagher et al (2013) and Muhammad et al (2019) also saw the need to reassess prescribed educational goals with the current needs of their countries.…”
Section: Purposes Of the Programsupporting
confidence: 90%
See 4 more Smart Citations
“…Results indicated that teachers highly observed the integration of national goals and the DepEd's Mission and Vision in the HUMSS curriculum. This result is consistent with Leduc (2010), however it was again in contrast to Aslan and Günay (2016), where teachers only viewed these elements as moderately observed. Similarly, Gallagher et al (2013) and Muhammad et al (2019) also saw the need to reassess prescribed educational goals with the current needs of their countries.…”
Section: Purposes Of the Programsupporting
confidence: 90%
“…This high perception means that the specific goals of these disciplines were well-articulated and well-observed in the curriculum. In contrast to Aslan and Günay (2016), teachers only had a moderate level of opinions on curricular elements. For Kallendorf (2002), this alignment of the HUMSS curriculum may produce literate citizens who can speak and write with clarity, who are active in the community, and who can make sensible decisions.…”
Section: Alignment To Humanities and Social Sciences Disciplinesmentioning
confidence: 89%
See 3 more Smart Citations